2016
DOI: 10.17718/tojde.09269
|View full text |Cite
|
Sign up to set email alerts
|

Information Needs of Distance Learners: A Case of Winneba Study Center, University of Education, Winneba, Ghana

Abstract: The study focuses on the information needs of distance learners of the Winneba Study Centre of the University of Education, Winneba. The main objective was to investigate the information needs of this group of students who live far away from their host institution and have minimal interaction with their tutors. The study was a survey and made use of a questionnaire as research instrument. The target population consisted of all distance learners of the Centre; this includes the Diploma and Post Diploma students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…It is not enough for academic institutions to raise students' awareness about the use of DL tools; it is now in this context that researchers are working to improve the understanding, availability, and use of DL. According to some studies, the knowledge and use of DL around the world have revealed a range of barriers preventing learners from using online library resources [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is not enough for academic institutions to raise students' awareness about the use of DL tools; it is now in this context that researchers are working to improve the understanding, availability, and use of DL. According to some studies, the knowledge and use of DL around the world have revealed a range of barriers preventing learners from using online library resources [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Even though many successes have been chalked since it was implemented in Ghana's educational system (Adu, 2019), a lot of teething problems continue to bedevil the successful implementation of this distance education. Among these include the lack of purpose-built academic library services to distance learners and other members of the distance learning community (Larson & Owusu-Acheaw, 2016). Among other factors (Owusu-Ansah et al, 2018b), administrators and some academic librarians in conventional universities, that have also integrated distance education, make a false assumption that distance learners in their institutions use and or are satisfied with the existing library resources simply because those resources are online.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The University of Education, Winneba's digital library provides strategic support to the University's mandate of providing cutting edge teaching, learning and research in teacher education and its performance has not been in doubt (Owusu-Ansah et al, 2018a;Owusu-Ansah & Takyi, 2017). However, previous evidence points to an unsatisfactory distance learning library service at the university (Larson & Owusu-Acheaw, 2016;Owusu-Ansah et al, 2018b). There is a need for academic libraries in conventional universities providing distance education to re-align traditional library resources to suit the needs of the distance education community (Ahenkorah-Marfo & Nikoi, 2019).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In distance learning institutions where digital libraries have been deployed, both librarians and academics often assume that distance learners use digital libraries resources to achieve learning outcomes. The existing academic and information practices of distance education stakeholders, however, appears to suggest that there are no policies in place to ensure the use of digital library resources in distance education (Larson and Owusu-Acheaw, 2016; Owusu-Mensah et al, 2015). This situation has direct ramifications for the development of appropriate digital content, sustainable funding, technological infrastructure and skills development to enable usage of digital library resources in distance education.…”
Section: Digital Library Services At the University Of Education Winmentioning
confidence: 99%
“…For instance, the Centre may decide to subscribe to the ERIC Database, a very essential digital resource for educators and education researchers, which is currently not among the electronic resources of the University. A separate financial allocation for distance learning library services may also be useful for specialised training for librarians involved in distance education (Larson and Owusu-Acheaw, 2012). Finally, it is suggested that librarians should collaborate actively with distance education stakeholders to develop digital library services in distance education at the University.…”
Section: Recommendationsmentioning
confidence: 99%